Positive electrode active material having a core-shell structure and manufacturing method thereof, positive electrode plate, secondary battery, battery module, battery pack and power consumption device

By adjusting the elemental impurity mass in the lithium calcium manganate positive electrode active material and adopting a double-layer coating structure, the problems of Li/Mn reverse position defect and manganese ion release are solved, and the capacity, circulation performance and safety performance of the battery are improved.

JP7661604B2Active Publication Date: 2025-04-14CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024501212
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-06-17
Publication Date
2025-04-14
Estimated Expiration
2042-06-17

AI Technical Summary

Technical Problem

Traditional lithium calcium manganate positive electrode live materials are prone to Li/Mn inverse defects and manganese ions release during charging and discharging, resulting in reduced battery capacity and poor safety performance and cycling performance.

Method used

By simultaneously adjusting the impurity of specific elements at the Li, Mn, P and O positions, crystalline phosphate dioxide and oxides are used as the first coating, and a second coating containing carbon is applied thereon to form a positive electrode living material with a core-shell structure.

Benefits of technology

It significantly reduces the occurrence of Li/Mn inverse defects, reduces the release of manganese ions, and improves the capacity, circulation performance, high-temperature storage performance and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661604000052
    Figure 0007661604000052
  • Figure 0007661604000053
    Figure 0007661604000053
  • Figure 0007661604000054
    Figure 0007661604000054
Patent Text Reader

Abstract

The present application provides a positive electrode active material having a core-shell structure, a method for producing the positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consumption device, and the positive electrode active material is Li m A x Mn 1-y B y P 1-z C z O 4-n D n A core containing a crystalline pyrophosphate M a P2O7 and oxide M' b O c and a second coating layer containing carbon and coating the first coating layer. The positive electrode active material of the present application can reduce the generation of Li / Mn antisite defects, reduce the elution of manganese, reduce the lattice change rate, improve the capacity of the secondary battery, and improve the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of secondary batteries, in particular to a positive electrode active material having a core-shell structure, a method for producing the positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. As secondary batteries have made great strides in development, their energy density, cycle performance and safety performance are also required to be higher. As a conventional positive electrode active material of secondary batteries, lithium manganese phosphate is prone to Li / Mn antisite defects during charging and discharging, and manganese leaching is relatively serious, which affects the gram capacity of secondary batteries and causes the safety performance and cycle performance of secondary batteries to be poor. Summary of the Invention [Means for solving the problem]

[0003] The present application has been made in view of the above-mentioned problems, and its objective is to provide a core-shell structured cathode active material, a manufacturing method for the cathode active material, a cathode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, which solve the problems of conventional lithium manganese phosphate cathode active materials being prone to Li / Mn antisite defects during charge and discharge and relatively serious manganese elution, thereby solving the problems of low capacity, poor safety performance, and poor cycle performance of secondary batteries.

[0004] In order to achieve the above object, a first aspect of the present application provides a positive electrode active material having a core-shell structure, the positive electrode active material including a core and a shell covering the core, The core is Li m A xMn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.5-1.2, and optionally from any number in the range of 0.9-1.1; x is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; y is selected from any number in the range of 0.001-0.5; z is selected from any number in the range of 0.001-0.2, and optionally from any number in the range of 0.001-0.1; n is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; and A is Zn, Al, Na, K, Mg. , Nb, Mo and W, and optionally one or more elements selected from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; The shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer, Here, the first coating layer is made of crystalline pyrophosphate M a P2O7 and oxide M' b O cwherein a is greater than 0 and less than or equal to 4, and optionally greater than 0 and less than or equal to 3; b is greater than 0 and less than or equal to 2; c is greater than 0 and less than or equal to 5; M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li and Fe; M' is an alkali metal, an alkaline earth metal, a transition metal, a Group IIIA element, a Group IVA element, a lanthanum, one or more elements selected from titanium-based elements and Sb, and optionally one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and further optionally one or more elements selected from Mg, Al, V, Cu, Zn, Zr and W; The second coating layer includes carbon.

[0005] The inventors of the present application have found that in actual work, the lithium manganese phosphate positive electrode active material is prone to Li / Mn antisite defects during deep charging and discharging, and manganese leaching is relatively serious. The leached manganese is reduced to metal manganese after transitioning to the negative electrode. These generated metal manganese correspond to a "catalyst" and can catalyze the decomposition of the SEI film (solid electrolyte interphase) on the surface of the negative electrode. Some of the generated by-products are gases, which are prone to causing battery expansion and affecting the safety performance of the secondary battery, and another part is deposited on the surface of the negative electrode, obstructing the channel through which lithium ions enter and exit the negative electrode, increasing the impedance of the secondary battery, and affecting the dynamic performance and cycle performance of the battery. In addition, in order to compensate for the lost SEI film, the electrolyte and active lithium inside the battery are constantly consumed, which has an irreversible effect on the capacity retention rate of the secondary battery.

[0006] As a result, the applicant has unexpectedly discovered that by simultaneously doping specific elements in specific amounts into the Li site, Mn site, P site and O site of the compound LiMnPO4, coating the surface of the compound with a first coating layer containing crystalline pyrophosphate and oxide, and coating the surface of the first coating layer with a second coating layer containing carbon, to obtain a positive electrode active material, the occurrence of Li / Mn antisite defects can be greatly reduced, the elution of manganese can be reduced, and the lattice change rate can be decreased, so as to improve the capacity of the secondary battery, and the cycle performance, high-temperature storage performance and safety performance of the secondary battery.

[0007] Unless otherwise noted, the chemical formula is Li m A x Mn 1-y B y P 1-z C z O 4-n D n In the above, when A is two or more elements, the above-mentioned limit on the numerical range of x not only limits the stoichiometric number of each type of element that constitutes A, but also limits the sum of the stoichiometric numbers of each element that constitutes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers x1, x2...xn of A1, A2...An must all be within the numerical range in which the application limits x, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C, and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C, and D in the present application also has the above-mentioned meaning.

[0008] Unless otherwise specified, the chemical formula M a In P2O7, when M is two or more elements, the above-mentioned limit of the numerical range of a not only limits the stoichiometric number of each type of element that is M, but also limits the sum of the stoichiometric numbers of each element that is M. For example, when M is two or more elements M1, M2...Mn, the stoichiometric numbers a1, a2...an of M1, M2...Mn must all be within the numerical range in which the present application limits a, and the sum of a1, a2...an must also be within this numerical range. Similarly, in the chemical formula M' b O cWhen M' in is two or more elements, the limitations of the numerical range of the stoichiometric number b of M' in this application also have the above meaning.

[0009] In any embodiment of the first aspect, the lattice spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm and the angle with respect to the (111) crystal direction is 26.41°-32.57°; Optionally, the lattice spacing of the pyrophosphate in the first coating layer is 0.300-0.310 nm; and / or Optionally, the angle with respect to the (111) crystal direction of the pyrophosphate in the first coating layer is 29.00°-30.00°.

[0010] When the angle between the lattice spacing of the pyrophosphate in the first coating layer and the crystal direction (111) is within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.

[0011] In any embodiment of the first aspect, x is any number in the range of 0.001-0.005; and / or y is any number in the range of 0.01-0.5, optionally any number in the range of 0.25-0.5; and / or z is any number in the range of 0.001-0.005, and / or n is any number in the range of 0.001-0.005.

[0012] Therefore, when x, y, z, and n are within the above ranges, the generation of Li / Mn antisite defects can be further reduced, the elution of manganese can be reduced, and the lattice change rate can be reduced, thereby further improving the capacity of the secondary battery and improving the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.

[0013] In any embodiment of the first aspect, in the core, the ratio of 1-y to y is 1 to 4, and optionally 1.5 to 3, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above conditions are met, the energy density and cycle performance of a secondary battery manufactured using the positive electrode active material can be further improved.

[0014] In any embodiment of the first aspect, in the core, the ratio of m to x is 1 to 1200, optionally 9 to 1100, and further optionally 190-998, where x represents the sum of the stoichiometric numbers of elements doped into the Li site. When the above conditions are met, the energy density and cycle performance of a secondary battery manufactured using the positive electrode active material can be further improved.

[0015] In any embodiment of the first aspect, the coverage of the first coating layer is greater than 0% and up to 7% by weight, optionally 4-5.6% by weight, based on the weight of the core.

[0016] When the coating amount of the first coating layer is within the above range, the elution of manganese can be further suppressed, the transmission of lithium ions can be further promoted, the low impedance of the secondary battery can be maintained, and the dynamic performance of the secondary battery can be improved.

[0017] In any embodiment of the first aspect, the weight ratio of pyrophosphate to oxide in the first coating layer is from 1:3 to 3:1, optionally from 1:3 to 1:1.

[0018] By adjusting the compounding ratio of the pyrophosphate and the oxide appropriately, it is advantageous to fully utilize the synergistic effect of the two, and it is possible to further suppress the elution of manganese and maintain a relatively low impedance of the secondary battery.

[0019] In any embodiment of the first aspect, the crystallinity of the pyrophosphate in the first coating layer is between 10% and 100%, optionally between 50% and 100%.

[0020] In the first coating layer of the lithium manganese phosphate positive active material of the present application, the pyrophosphate with a certain degree of crystallinity is advantageous for maintaining the structural stability of the first coating layer and reducing lattice defects, which is advantageous for the pyrophosphate to fully exert the effect of preventing manganese elution on the one hand, and is also advantageous for reducing the heterolithium content on the surface and reducing the valence state of surface oxygen, thereby reducing the interfacial side reaction between the positive electrode material and the electrolyte, reducing the consumption of the electrolyte, and improving the cycle performance and safety performance of the secondary battery.

[0021] In any embodiment of the first aspect, the coverage of the second coating layer is greater than 0% and up to 6% by weight, optionally 3-5% by weight, based on the weight of the core.

[0022] The carbon-containing layer, which is the second coating layer, on the one hand, exerts a "barrier" function and avoids direct contact between the positive electrode active material and the electrolyte, thereby reducing the corrosion of the active material by the electrolyte and improving the safety performance of the battery at high temperatures. On the other hand, it has a relatively strong conductive ability and can improve the dynamic performance of the secondary battery by reducing the internal resistance of the battery. When the coating amount of the second coating layer is within the above range, the dynamic performance and safety performance of the secondary battery can be further improved under the premise of maintaining a relatively high gram capacity of the positive electrode active material.

[0023] In any embodiment of the first aspect, in the cathode active material, A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo, and W, and optionally A is Mg or Nb; and / or B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, alternatively B is at least two elements selected from Fe, Ti, V, Co and Mg, further alternatively B is a combination of the element Fe with at least one element selected from Ti, V, Co and Mg, and / or C is any one element selected from B, S, Si and N, optionally C is S, and / or D is any one element selected from S, F, Cl and Br, and optionally, D is F.

[0024] Selecting the doping element within the above range is advantageous for reinforcing the doping effect, on the one hand, further reducing the lattice change rate, thereby inhibiting the dissolution of manganese and reducing the consumption of the electrolyte and active lithium, and on the other hand, further reducing the oxygen activity on the surface and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the battery.

[0025] In any embodiment of the first aspect, the positive electrode active material has a Li / Mn antisite defect concentration of 4% or less, and optionally 2% or less. In the positive electrode active material of the present application, the Li / Mn antisite defect is a defect that is a LiMnPO4 lattice defect that is formed by dissociating Li + and Mn 2+ The position of Li is exchanged. + The transmission channel is a one-dimensional channel, and Mn 2+ Li + The antisite defect Mn 2+ Li + By suppressing the Li / Mn antisite defect concentration to a low level, the gram capacity of the positive electrode active material and the rate performance of the secondary battery can be improved.

[0026] In any embodiment of the first aspect, the lattice change rate before and after the positive electrode active material completely releases lithium is 9.8% or less, optionally 6% or less, and more optionally 4% or less. The lithium release process of LiMnPO4 is a two-phase reaction. The interface stress between the two phases is determined by the magnitude of the lattice change rate. The smaller the lattice change rate and the smaller the interface stress, the greater the Li + Therefore, the decrease in the lattice change rate of the core is +This is advantageous in reinforcing the transmission capability of the secondary battery, thereby improving the rate performance of the secondary battery.

[0027] In any embodiment of the first aspect, the valence state of the surface oxygen of the positive electrode active material is -1.55 or less, optionally -1.88 or less, and more optionally -1.98 to -1.88. This is because the higher the valence state of the oxygen compound, the higher its ability to obtain electrons, i.e., its oxidizing property. On the other hand, in the positive electrode active material of the present application, the surface valence state of oxygen is controlled to a relatively low level, thereby reducing the reaction activity of the positive electrode material surface and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery.

[0028] In any embodiment of the first aspect, the positive electrode active material has a packed density at 3 tonnes (T) of 1.89 g / cm 3 or more, and optionally 2.0 g / cm 3 or more, and more selectively, 2.2 g / cm 3 The higher the compaction density of the positive electrode active material, i.e., the greater the weight of the active material per unit volume, the more advantageous it is for increasing the volumetric energy density of the secondary battery.

[0029] A second aspect of the present application provides a method for producing a positive electrode active material, the method comprising: Providing a core material, the core comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D nwherein m is selected from any number in the range of 0.5-1.2, and optionally from any number in the range of 0.9-1.1; x is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; y is selected from any number in the range of 0.001-0.5; z is selected from any number in the range of 0.001-0.2, and optionally from any number in the range of 0.001-0.1; n is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; and A is Zn, Al, Na, K, Mg, Nb , Mo and W, and optionally one or more elements selected from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; Pyrophosphate M a Powder containing P2O7, a carbon source and an oxide M' b O c providing a suspension comprising a core material and a M containing pyrophosphate; a P2O7 powder and a carbon source and oxide M' b O cand sintering to obtain a positive electrode active material, wherein a is greater than 0 and less than 4, and optionally greater than 0 and less than 3; b is greater than 0 and less than 2; c is greater than 0 and less than 5; M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally greater than Li and Fe; M' is an alkali metal, an alkaline earth metal, a transition metal, a Group IIIA element, a Group IV element, a coating step of one or more elements selected from the group A elements, the lanthanide elements and Sb, and optionally one or more elements selected from the group Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and optionally one or more elements selected from the group Mg, Al, V, Cu, Zn, Zr and W; Here, the positive electrode active material has a core-shell structure, and this positive electrode active material includes a core and a shell that covers the core. The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n The shell comprises a first coating layer covering the core and a second coating layer covering the first coating layer, and the first coating layer is a crystalline pyrophosphate M a P2O7 and oxide M' b O c and the second coating layer comprises carbon.

[0030] As a result, the applicant has unexpectedly discovered that by simultaneously doping specific elements in specific amounts into the Li site, Mn site, P site and O site of the compound LiMnPO4, coating the surface of the compound with a first coating layer containing crystalline pyrophosphate and oxide, and coating the surface of the first coating layer with a second coating layer containing carbon, to obtain a positive electrode active material, the occurrence of Li / Mn antisite defects can be greatly reduced, the elution of manganese can be reduced, and the lattice change rate can be decreased, so as to improve the capacity of the secondary battery, and the cycle performance, high-temperature storage performance and safety performance of the secondary battery.

[0031] In any embodiment of the second aspect of the present application, the step of providing a core material comprises: (1) mixing a source of manganese, a source of element B, an acid and a selective solvent to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, and a source of element D, and an optional solvent, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

[0032] In any embodiment of the second aspect of the present application, step (1) comprises mixing at 60° C.-120° C. and / or mixing in step (1) with stirring at a rotation speed of 200-800 rpm.

[0033] In any embodiment of the second aspect of the present application, in step (2), the mixing is carried out for 8-15 hours.

[0034] In any embodiment of the second aspect of the present application, in step (2), sintering is carried out at 600° C.-900° C. for 6-14 hours.

[0035] In an optional embodiment of the second aspect of the present application, the source of element A is one or more selected from the group consisting of an element A, an oxide, a phosphate, an oxalate, a carbonate and a sulfate, and / or the source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The source of element D is one or more selected from a simple substance and an ammonium salt of element D.

[0036] In any embodiment of the second aspect of the present application, pyrophosphate M a The powder containing P2O7 is produced by the following steps: A source of element M, a phosphorus source and an optional solvent are mixed to obtain a mixture, the pH of the mixture is adjusted to 4-6, and the mixture is kept mixed, dried and sintered.

[0037] In any embodiment of the second aspect of the present application, pyrophosphate M a In the step of preparing the powder containing P2O7, drying is drying at 100°C-300°C for 4-8h, optionally drying at 150°C-200°C, and / or sintering is sintering at 500°C-800°C and under inert gas protection for 4-10h, optionally sintering at 650°C-800°C.

[0038] In any embodiment of the second aspect of the present application, the sintering temperature in the coating step is 500-800° C. and the sintering time is 4-10 h.

[0039] A third aspect of the present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the production method of the second aspect of the present application, and the content of the positive electrode active material in the positive electrode film layer is 10 wt % or more based on the total weight of the positive electrode film layer.

[0040] In any embodiment of the third aspect of the present application, the content of the positive active material in the positive electrode membrane layer is 90-99.5 wt % based on the total weight of the positive electrode membrane layer, thereby ensuring that the secondary battery has a relatively high capacity and relatively good cycle performance, high-temperature storage performance and safety performance.

[0041] A fourth aspect of the present application provides a secondary battery, the secondary battery including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the production method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.

[0042] A fifth aspect of the present application provides a battery module, the battery module including the secondary battery of the fourth aspect of the present application.

[0043] A sixth aspect of the present application provides a battery pack, the battery pack including the battery module of the fifth aspect of the present application.

[0044] A seventh aspect of the present application provides a power consumption device, the power consumption device including at least one selected from a secondary battery of the fourth aspect of the present application, a battery module of the fifth aspect of the present application, and a battery pack of the sixth aspect of the present application. [Brief description of the drawings]

[0045] [Figure 1] FIG. 1 is a schematic diagram of a positive electrode active material having a core-shell structure according to one embodiment of the present application. [Diagram 2] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Diagram 3] FIG. 3 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 2. [Figure 4] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Diagram 5] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Figure 6] FIG. 6 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 5. [Figure 7] 1 is a schematic diagram of a power consumption device that uses a secondary battery as a power source according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] Hereinafter, with reference to the drawings, embodiments specifically disclosing the positive electrode active material, the method for manufacturing the positive electrode active material, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0047] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0048] In this application, the ranges "less than or equal to a certain value" and "greater than or equal to a certain value" indicate ranges defined by a certain value as the upper or lower limit.

[0049] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0050] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0051] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, a method including steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, a method described may further include step (c) means that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0052] Unless otherwise stated, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.

[0053] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0054] Unless otherwise specified, in this application, the median particle size D v 50 is the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode active material reaches 50%. In this application, the median particle size Dv 50 can be measured using laser diffraction particle size analysis, for example see standard GB / T 19077-2016, using a laser particle size analyzer (e.g. Malvern Master Size 3000).

[0055] Unless otherwise specified, in this application, the term "coating layer" refers to a layer of material coated on a core, the layer of material may completely or partially cover the core, and the term "coating layer" is used merely for ease of description and is not intended to limit the present invention. Similarly, the term "thickness of the coating layer" refers to the thickness of the layer of material coated on the core in the radial direction of the core.

[0056] Unless otherwise specified, in this application, the term "source" refers to a compound that is a source of an element, and illustrative types of "source" include, but are not limited to, carbonates, sulfates, nitrates, elements, halides, oxides, and hydrogen oxides.

[0057] [Secondary battery] A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be continuously used by activating the active material by charging after discharging the battery.

[0058] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During charging and discharging of the battery, active ions (e.g., lithium ions) shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short-circuiting between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive electrode plate and the negative electrode plate.

[0059] [Cathode active material] The present application provides a positive electrode active material having a core-shell structure, the positive electrode active material including a core and a shell covering the core, The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D nwherein m is selected from any number in the range of 0.5-1.2, and optionally from any number in the range of 0.9-1.1; x is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; y is selected from any number in the range of 0.001-0.5; z is selected from any number in the range of 0.001-0.2, and optionally from any number in the range of 0.001-0.1; n is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; and A is Zn, Al, Na, K, Mg. , Nb, Mo and W, and optionally one or more elements selected from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; The shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer, Here, the first coating layer is made of crystalline pyrophosphate M a P2O7 and oxide M' b O cwherein a is greater than 0 and less than or equal to 4, and optionally greater than 0 and less than or equal to 3; b is greater than 0 and less than or equal to 2; c is greater than 0 and less than or equal to 5; M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally one or more elements selected from Li and Fe; M' is an alkali metal, an alkaline earth metal, a transition metal, a Group IIIA element, a Group IVA element, a lanthanum, one or more elements selected from titanium-based elements and Sb, and optionally one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and further optionally one or more elements selected from Mg, Al, V, Cu, Zn, Zr and W; The second coating layer includes carbon.

[0060] As shown in Fig. 1, the positive electrode active material having a core-shell structure of the present application includes a core 11, a first coating layer 12 that coats the core 11, and a second coating layer 13 that coats the first coating layer 12. Here, the core 11 is Li m A x Mn 1-y B y P 1-z C z O 4-n D nIn the core 11, the lattice change rate is reduced by doping Li and Mn sites, the Mn site doping can also effectively reduce the surface activity, thereby suppressing the dissolution of Mn and the interfacial side reaction between the positive electrode active material and the electrolyte, the P site doping makes the change rate of Mn-O bond length faster and reduces the small polaron transition barrier of the material, which is favorable for the electronic conductivity, the O site doping has a good effect on reducing the interfacial side reaction, the P site and O site doping further affects the dissolution of Mn of antisite defects and the dynamic performance, so the doping can reduce the antisite defect concentration in the material, improve the dynamic performance and gram capacity of the material, and can also change the topography of the particles, thereby increasing the compaction density. The first coating layer 12 includes a crystalline pyrophosphate and an oxide, and the transition barrier in the transition metal pyrophosphate is relatively high (>1 eV), so that the dissolution of the transition metal can be effectively suppressed. However, the oxide has high structural stability and low surface activity, so that the oxide coating can effectively reduce the interface side reaction, thereby improving the performance of the battery such as high-temperature cycle and high-temperature storage. In addition, since the second coating layer 13 is a carbon-containing layer, the conductive performance and desolvation ability of the positive electrode active material can be effectively improved. In addition, the "barrier" action of the second coating layer 13 can further inhibit the transition of manganese ions to the electrolyte and reduce the corrosion of the active material by the electrolyte. Therefore, the positive electrode active material of the present application reduces the occurrence of Li / Mn antisite defects by performing element doping and surface coating on lithium manganese phosphate, effectively suppresses the dissolution of Mn during lithium release, and promotes the transition of lithium ions, thereby improving the rate performance of the battery core and improving the cycle performance, high-temperature performance and safety performance of the secondary battery. It should be noted that the position of the main characteristic peak of the positive electrode active material of the present application is almost consistent with that before doping with LiMnPO4, which indicates that there is no impurity phase in the doped lithium manganese phosphate positive electrode active material, and the improvement of secondary battery performance is mainly due to element doping, not due to the impurity phase.

[0061] In some embodiments, Li m A x Mn 1-y B y P 1-z C z O 4-n D n The whole maintains electrical neutrality.

[0062] Unless otherwise noted, the chemical formula is Li m A x Mn 1-y B y P 1-z C z O 4-n D n In the above, when A is two or more elements, the above-mentioned limit on the numerical range of x not only limits the stoichiometric number of each type of element that constitutes A, but also limits the sum of the stoichiometric numbers of each element that constitutes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers x1, x2...xn of A1, A2...An must all be within the numerical range in which the application limits x, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C, and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C, and D in the present application also has the above-mentioned meaning.

[0063] Unless otherwise specified, M in the chemical formula a In P2O7, when M is two or more elements, the above-mentioned limit of the numerical range of a not only limits the stoichiometric number of each type of element that is M, but also limits the sum of the stoichiometric numbers of each element that is M. For example, when M is two or more elements M1, M2...Mn, the stoichiometric numbers a1, a2...an of M1, M2...Mn must all be within the numerical range in which the present application limits a, and the sum of a1, a2...an must also be within this numerical range. Similarly, in the chemical formula M' b O c When M' in is two or more elements, the limitations of the numerical range of the stoichiometric number b of M' in this application also have the above meaning.

[0064] In some embodiments, when A is one, two, three or four elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A x Q x1 H x2 E x3 K x4 where x1+x2+x3+x4=x, and x1, x2, x3, and x4 are all positive numbers and not zero at the same time, and Q, H, E, and K are each independently one selected from Zn, Al, Na, K, Mg, Nb, Mo, and W. Optionally, one of x1, x2, x3, and x4 is zero and the remaining is not zero, and further optionally, two of x1, x2, x3, and x4 are zero and the remaining is not zero, and further optionally, three of x1, x2, x3, and x4 are zero and the remaining is not zero. Core Li m A x Mn 1-y B y P 1-z C z O 4-n D n In the present invention, it is advantageous to dope one, two, three or four of the above A elements into the Li site, and selectively dope one, two or three of the above A elements into the Mn site, one or two B elements into the Phosphorus site, and one or two C elements into the O site, which are advantageous for uniformly distributing the doping elements.

[0065] In some embodiments, the values ​​of m, x, y, z and n satisfy the requirement to maintain electrical neutrality throughout the core.

[0066] Core Li m A x Mn 1-y B y P 1-z C z O 4-n D nIn this, the magnitude of m is influenced by the magnitude of the valence states of A, B, C, D and the magnitudes of x, y, z and n to ensure that the whole system exhibits electrical neutrality. If the value of m is too small, it will reduce the lithium content of the whole core system and affect the gram capacity of the material. The values ​​of x, y, z, and n limit the total amount of all doping elements, if the doping amount is too small, the doping element will not function, and if y is more than 0.5, the content of Mn in the system will be low, which will affect the voltage plateau of the material. The C element is doped at the P position, and the PO tetrahedron is relatively stable, but if the z value is too large, it will affect the stability of the material, so the z value is limited to 0.001-0.2.

[0067] In addition, maintaining the electrical neutrality of the entire core system can ensure that defects and heterophases in the positive electrode active material are minimized. When an excess transition metal (e.g., manganese) is present in the positive electrode active material, the structure of the material system itself is relatively stable, and the excess transition metal is likely to precipitate in the form of an element or form a heterophase inside the lattice, and by maintaining electrical neutrality, such heterophases can be minimized. In addition, ensuring the electrical neutrality of the system can also improve the kinetic performance of the material by generating lithium vacancies in the material in some cases.

[0068] Process control (e.g., thoroughly mixing and grinding various source materials) can ensure that each element is uniformly distributed in the lattice without aggregation. The main feature peak position in the XRD diagram of lithium manganese phosphate after element doping is consistent with that of undoped LiMnPO4, indicating that no impurity phase is introduced in the doping process, so the improvement of core performance is mainly due to element doping, not due to heterophase. After producing the positive electrode active material, the inventor of the present application cut out the middle region of the already produced positive electrode active material particle by focused ion beam (abbreviated as FIB), and tested it by transmission electron microscope (abbreviated as TEM) and X-ray spectroscopy (abbreviated as EDS), and found that each element is uniformly distributed without aggregation.

[0069] In some embodiments, the values ​​of a, b and c are M a P2O7 and M' b O c The condition of maintaining electrical neutrality is met.

[0070] In some embodiments, the lattice spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm and the angle with respect to the (111) crystal direction is 26.41°-32.57°; Optionally, the lattice spacing of the pyrophosphate in the first coating layer is 0.300-0.310 nm (e.g., 0.303 nm); and / or Optionally, the angle with the (111) crystal direction of the pyrophosphate in the first coating layer is 29.00°-30.00° (eg, 29.496°).

[0071] When the angle between the lattice spacing of the pyrophosphate in the first coating layer and the crystal direction (111) is within the above range, the impurity phase in the coating layer can be effectively avoided, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.

[0072] In some embodiments, x is any number in the range of 0.001-0.005; and / or y is any number in the range of 0.01-0.5, optionally any number in the range of 0.25-0.5; and / or z is any number in the range of 0.001-0.005, and / or n is any number in the range of 0.001-0.005.

[0073] Therefore, when x, y, z, and n are within the above ranges, the generation of Li / Mn antisite defects can be further reduced, the elution of manganese can be reduced, and the lattice change rate can be reduced, thereby further improving the capacity of the secondary battery and improving the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.

[0074] In some embodiments, in the core, the ratio of 1-y to y is 1 to 4, and optionally 1.5 to 3, where y represents the sum of the stoichiometric numbers of elements doped into the Mn site. When the above conditions are met, the energy density and cycle performance of a secondary battery manufactured using the positive electrode active material can be further improved.

[0075] In some embodiments, the ratio of m to x in the core is 1-1200, optionally 9-1100, and further optionally 190-998, where x represents the sum of the stoichiometric numbers of elements doped into the Li site. When the above conditions are met, the energy density and cycle performance of a secondary battery manufactured using the positive electrode active material can be further improved.

[0076] In some embodiments, the coverage of the first coating layer is greater than 0% and up to 7% by weight, optionally 4-5.6% by weight, based on the weight of the core.

[0077] When the coating amount of the first coating layer is within the above range, the elution of manganese can be further suppressed, the transmission of lithium ions can be further promoted, the low impedance of the secondary battery can be maintained, and the dynamic performance of the secondary battery can be improved.

[0078] In some embodiments, the weight ratio of pyrophosphate to oxide in the first coating layer is from 1:3 to 3:1, and optionally from 1:3 to 1:1.

[0079] By adjusting the compounding ratio of the pyrophosphate and the oxide appropriately, it is advantageous to fully utilize the synergistic effect of the two, and it is possible to further suppress the elution of manganese and maintain a relatively low impedance of the secondary battery.

[0080] In some embodiments, the thickness of the first coating layer is 1-100 nm, so that the transition barrier of the transition metal in the first coating layer is relatively high, and the dissolution of the transition metal can be effectively reduced. The oxide of the transition metal has relatively high stability, and the interface side reaction can be effectively reduced, thereby improving the high temperature stability of the material.

[0081] In some embodiments, the second coating layer has a thickness of 1-100 nm.

[0082] In some embodiments, the crystallinity of the pyrophosphate in the first coating layer is between 10% and 100%, optionally between 50% and 100%.

[0083] In the first coating layer of the lithium manganese phosphate positive active material of the present application, the pyrophosphate with a certain degree of crystallinity is advantageous for maintaining the structural stability of the first coating layer and reducing lattice defects, which is advantageous for the pyrophosphate to fully exert the effect of preventing manganese elution on the one hand, and is also advantageous for reducing the heterolithium content on the surface and reducing the valence state of surface oxygen, thereby reducing the interfacial side reaction between the positive electrode material and the electrolyte, reducing the consumption of the electrolyte, and improving the cycle performance and safety performance of the secondary battery.

[0084] In some embodiments, the crystallinity of the first coating layer pyrophosphate of the positive electrode active material may be tested by common technical means in the art, such as density method, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance spectroscopy, and may be tested by, for example, X-ray diffraction method.

[0085] A specific method for testing the crystallinity of the pyrophosphate of the first coating layer of the positive electrode active material by X-ray diffraction may include the following steps.

[0086] A certain amount of positive electrode active material powder is taken and the total scattering intensity is measured by X-ray, which is the sum of the scattering intensity of the material in the entire space and has nothing to do with the order state of the sample, but only with the intensity of the primary radiation, the chemical structure of the positive electrode active material powder, and the total number of electrons involved in diffraction, i.e., the amount of mass. Crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, and the crystallinity is the ratio of the crystalline partial scattering to the total scattering intensity.

[0087] It should be noted that in some embodiments, the crystallinity of the pyrophosphate in the coating layer can be adjusted, for example, by adjusting the process conditions of the sintering process, such as sintering temperature, sintering time, and the like.

[0088] In some embodiments, the coverage of the second coating layer is greater than 0% and up to 6% by weight, optionally 3-5% by weight, based on the weight of the core.

[0089] The carbon-containing layer, which is the second coating layer, on the one hand, exerts a "barrier" function and avoids direct contact between the positive electrode active material and the electrolyte, thereby reducing the corrosion of the active material by the electrolyte and improving the safety performance of the battery at high temperatures. On the other hand, it has a relatively strong conductive ability and can improve the dynamic performance of the secondary battery by reducing the internal resistance of the battery. When the coating amount of the second coating layer is within the above range, the dynamic performance and safety performance of the secondary battery can be further improved under the premise of maintaining a relatively high gram capacity of the positive electrode active material.

[0090] In some embodiments, in the cathode active material, A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo, and W, and optionally A is Mg or Nb; and / or B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, alternatively B is at least two elements selected from Fe, Ti, V, Co and Mg, further alternatively B is a combination of the element Fe with at least one element selected from Ti, V, Co and Mg, and / or C is any one element selected from B, S, Si and N, optionally C is S, and / or D is any one element selected from S, F, Cl and Br, and optionally, D is F.

[0091] Selecting the doping element within the above range is advantageous for reinforcing the doping effect, on the one hand, further reducing the lattice change rate, thereby inhibiting the dissolution of manganese and reducing the consumption of the electrolyte and active lithium, and on the other hand, further reducing the oxygen activity on the surface and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the battery.

[0092] In some embodiments, the positive electrode active material has a Li / Mn antisite defect concentration of 4% or less, and optionally 2% or less. In the positive electrode active material of the present application, the Li / Mn antisite defect is a defect that is a LiMnPO4 lattice defect that is formed by displacing Li + and Mn 2+ The position of Li is exchanged. + The transmission channel is a one-dimensional channel, and Mn 2+ Li + The antisite defect Mn 2+ Li + By suppressing the Li / Mn antisite defect concentration to a low level, the gram capacity of the positive electrode active material and the rate performance of the secondary battery can be improved. In the present application, the antisite defect concentration can be measured, for example, according to JIS K 0131-1996.

[0093] In some embodiments, the lattice change rate before and after the positive electrode active material completely releases lithium is 9.8% or less, optionally 6% or less, and more preferably 4% or less. The lithium release process of LiMnPO4 is a two-phase reaction. The interface stress between the two phases is determined by the magnitude of the lattice change rate. The smaller the lattice change rate and the smaller the interface stress, the greater the Li + Therefore, the decrease in the lattice change rate of the core is + This is advantageous in reinforcing the transmission ability of the secondary battery, thereby improving the rate performance of the secondary battery. The lattice change rate can be measured by a method known in the art, for example, X-ray diffraction spectrum (XRD).

[0094] In some optional embodiments, the valence state of the surface oxygen of the positive electrode active material is -1.55 or less, optionally -1.88 or less, and more optionally -1.98 to -1.88. This is because the higher the valence state of the oxygen compound, the higher its ability to obtain electrons, i.e., its oxidizing property. On the other hand, in the positive electrode active material of the present application, the surface valence state of oxygen is controlled to a relatively low level, thereby reducing the reaction activity of the positive electrode material surface and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and high-temperature storage performance of the secondary battery. The valence state of the surface oxygen can be measured by a method known in the art, for example, by electron energy loss spectroscopy (EELS).

[0095] In some embodiments, the positive electrode active material has a packed density at 3 tonnes (T) of 1.89 g / cm 3 or more, and optionally 2.0 g / cm 3 More preferably, 2.2 g / cm 3 That is all. The higher the compaction density of the positive electrode active material, i.e., the larger the weight of the active material per unit volume, the more advantageous it is for increasing the volumetric energy density of the secondary battery. In this application, the compaction density can be measured, for example, according to GB / T 24533-2009.

[0096] In some embodiments, the button cell of the positive electrode active material has an average discharge voltage of 3.5 V or greater and a discharge gram capacity of 140 mAh / g or greater, optionally an average discharge voltage of 3.6 V or greater and a discharge gram capacity of 145 mAh / g or greater.

[0097] Although the average discharge voltage of undoped LiMnPO4 is 4.0V or more, its discharge gram capacity is relatively low, generally less than 120mAh / g, so the energy density is relatively low. By adjusting the lattice change rate by doping, its discharge gram capacity can be significantly increased, and when the average discharge voltage is slightly decreased, the overall energy density is obviously increased.

[0098] In some embodiments, m is selected from any number in the range of 0.97-1.01.

[0099] In some embodiments, x is selected from any number in the range of 0.001-0.005.

[0100] In some embodiments, y is selected from any number in the range of 0.25-0.5.

[0101] In some embodiments, a is any number in the range of 1-4, for example, a is 1, 2, 3, 4.

[0102] In some embodiments, b is any number in the range of 1-2, for example b1,2.

[0103] In some embodiments, c is any number in the range of 1-5, optionally any number in the range of 1-3, for example c is 1, 2, 3, 4, 5.

[0104] [Method of manufacturing positive electrode active material] The present application provides a method for producing a positive electrode active material, the method comprising: Providing a core material, the core comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D nwherein m is selected from any number in the range of 0.5-1.2, and optionally from any number in the range of 0.9-1.1; x is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; y is selected from any number in the range of 0.001-0.5; z is selected from any number in the range of 0.001-0.2, and optionally from any number in the range of 0.001-0.1; n is selected from any number in the range of 0.001-0.5, and optionally from any number in the range of 0.001-0.1; and A is Zn, Al, Na, K, Mg, Nb , Mo and W, and optionally one or more elements selected from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; Pyrophosphate M a Powder containing P2O7, a carbon source and an oxide M' b O c and providing a suspension comprising the core material and pyrophosphate M a Powder containing P2O7, a carbon source and an oxide M' b O cand sintering to obtain a positive electrode active material, wherein a is greater than 0 and less than 4, and optionally greater than 0 and less than 3; b is greater than 0 and less than 2; c is greater than 0 and less than 5; M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and optionally greater than Li and Fe; M' is an alkali metal, an alkaline earth metal, a transition metal, a Group IIIA element, an I a coating step of one or more elements selected from VA group elements, Lanthanide group elements and Sb, and optionally one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and further optionally one or more elements selected from Mg, Al, V, Cu, Zn, Zr and W; Here, the positive electrode active material has a core-shell structure, and this positive electrode active material includes a core and a shell that covers the core. The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n The shell comprises a first coating layer covering the core and a second coating layer covering the first coating layer, and the first coating layer is a crystalline pyrophosphate M a P2O7 and oxide M' b O c and the second coating layer comprises carbon, where A, B, C, D, M, M', m, x, y, z, n, a, b and c are as defined above.

[0105] As a result, the applicant has unexpectedly discovered that by simultaneously doping specific elements in specific amounts into the Li site, Mn site, P site and O site of the compound LiMnPO4, coating the surface of the compound with a first coating layer containing crystalline pyrophosphate and oxide, and coating the surface of the first coating layer with a second coating layer containing carbon, to obtain a positive electrode active material, the occurrence of Li / Mn antisite defects can be greatly reduced, the elution of manganese can be reduced, and the lattice change rate can be decreased, so as to improve the capacity of the secondary battery, and the cycle performance, high-temperature storage performance and safety performance of the secondary battery.

[0106] In some embodiments, the step of providing a core material comprises: (1) mixing a source of manganese, a source of element B, an acid and a selective solvent to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, and a source of element D, and an optional solvent, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

[0107] In some embodiments, step (1) is performed at 60° C.-120° C., optionally at 70° C.-120° C. (e.g., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.) and / or in step (1), the mixture is stirred at a rotation speed of 200-800 rpm (e.g., 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm), optionally for 1-9 h (further optionally for 3-7 h, e.g., about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, or about 9 hours).

[0108] In some embodiments, in step (2), the mixing is performed for 8-15 h (e.g., about 8 h, about 9 h, about 10 h, about 11 h, about 12 h, about 13 h, about 14 h, or about 15 h), optionally at a temperature of 20-120° C., optionally at a temperature of 40-120° C. (e.g., about 30° C., about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.).

[0109] When the temperature and time during the production process of the core particles are within the above ranges, the core obtained by the production and the positive electrode active material produced thereby have few lattice defects, which is advantageous in suppressing the elution of manganese and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and safety performance of the secondary battery.

[0110] In some embodiments, in step (2), the mixing is performed under conditions where the pH is 3.5-6, alternatively the pH is 4-6, and further alternatively the pH is 4-5. It should be noted that in the present application, the pH can be adjusted by methods commonly used in the art, for example, by adding an acid or a base.

[0111] In some optional embodiments, the mixture obtained in step (1) is filtered, dried, and ground to a particle size D v Manganese salt particles doped with element B, where 50 is 50-200 nm, are obtained, and the manganese salt particles doped with element B are used to mix with a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, and an optional solvent in step (2).

[0112] In some embodiments, optionally in step (2), the molar ratio of the mixture or manganese salt particles doped with element B to the lithium source and the phosphorus source is 1:0.4-2.1:0.1-2.1, optionally about 1:0.4-0.5:0.1-1.

[0113] In some embodiments, in step (2), sintering is performed at 600-900°C for 4-10 hours, and optionally sintering is performed at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Optionally, sintering is performed under a protective atmosphere of an inert gas or a mixture of an inert gas and a hydrogen gas, and more optionally, the protective atmosphere is a mixture of 70-90% by volume of nitrogen gas and 10-30% by volume of hydrogen gas. The sintering temperature and sintering time can be within any range of any of the above values, which can improve the crystallinity of the core, reduce the generation of heterophase, and maintain the particle size of the core constant, thereby improving the gram capacity and compaction density of the positive electrode active material, and improving the overall performance of the secondary battery, including the rate performance.

[0114] In some optional embodiments, in step (2), the drying is performed by spray drying equipment.

[0115] In some optional embodiments, step (2) includes grinding while mixing.

[0116] In some embodiments, the M comprises pyrophosphate. a P2O7 powder is produced by the following steps: A source of element M, a phosphorus source and an optional solvent are mixed to obtain a mixture, the pH of the mixture is adjusted to 4-6, and the mixture is kept mixed, dried and sintered.

[0117] In some embodiments, pyrophosphate M a In the step of preparing the powder containing P2O7, drying is drying at 100°C-300°C for 4-8h, optionally drying at 150°C-200°C, and / or sintering is sintering at 500°C-800°C and under inert gas protection for 4-10h, optionally sintering at 650°C-800°C.

[0118] In some embodiments, the sintering temperature in the coating step is 500-800° C. and the sintering time is 4-10 h.

[0119] The manufacturing method of the present application is not particularly limited with respect to the origin of the material, and the origin of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, phosphate, oxalate, carbonate, oxide, and hydrogen oxide, provided that the origin can achieve the purpose of the manufacturing method of the present application.

[0120] In some embodiments, the source of element A is selected from one or more of the following: an element, an oxide, a phosphate, an oxalate, a carbonate, and a sulfate of element A; and / or the source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The source of element D is one or more selected from a simple substance and an ammonium salt of element D.

[0121] In some embodiments, the source of element M is one or more selected from the group consisting of an elemental salt, a carbonate, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydrogen oxide of element M.

[0122] In some embodiments, the source of element M' is one or more selected from the element M' simple salt, carbonate, sulfate, halide, nitrate, organic acid salt, oxide and hydrogen oxide.

[0123] The amount of each of the sources of elements A, B, C, D, M, M' added depends on the target doping amount, and the ratio of the amounts of the lithium source, manganese source and phosphorus source used is in accordance with the stoichiometric ratio.

[0124] In the present application, the manganese source may be any manganese-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the manganese source may be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.

[0125] In this application, acids include hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, silicic acid, metasilicic acid, etc. inorganic The acid may be one or more selected from an acid and an organic acid, such as oxalic acid, hi some embodiments, the acid is a dilute organic acid at a concentration of 60% by weight or less.

[0126] In the present application, the lithium source may be any lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the lithium source may be one or more selected from lithium carbonate, lithium hydride, lithium phosphate, and lithium dihydrogen phosphate.

[0127] In the present application, the phosphorus source may be any phosphorus-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0128] In the present application, by way of example, the carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, citric acid.

[0129] [Positive electrode plate] The present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material described above or the positive electrode active material produced by the production method described above, and a content of the positive electrode active material in the positive electrode film layer is 10 wt % or more based on the total weight of the positive electrode film layer.

[0130] In some embodiments, the content of the positive electrode active material in the positive electrode film layer is 90-99.5 wt % based on the total weight of the positive electrode film layer, ensuring that the secondary battery has a relatively high capacity and relatively good cycle performance, high temperature storage performance and safety performance.

[0131] In some embodiments, the positive electrode current collector may employ a metal foil sheet or a composite current collector. For example, an aluminum foil may be employed as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0132] In some embodiments, the positive electrode film layer may further include other positive electrode active materials for batteries known in the art. For example, the positive electrode active material may include at least one material selected from the group consisting of lithium-containing phosphates with an olivine structure and modified compounds thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0133] In some embodiments, the positive electrode membrane layer further optionally includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0134] In some embodiments, the positive electrode membrane layer further optionally includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.

[0135] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0136] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0137] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0138] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone alone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0139] In some embodiments, the negative electrode membrane layer further optionally includes an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS), for example.

[0140] In some embodiments, the negative electrode film layer further optionally includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.

[0141] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0142] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0143] [Electrolyte] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0144] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0145] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0146] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0147] In some embodiments, the electrolyte solution further optionally includes additives. For example, the additives may include an anode film-forming additive, a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, etc.

[0148] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.

[0149] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, without any particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0150] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0151] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.

[0152] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0153] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. For example, FIG. 2 shows a secondary battery 5 having a rectangular structure as an example.

[0154] In some embodiments, referring to FIG. 3, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected on the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be installed on the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can be formed into an electrode assembly 52 through a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.

[0155] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.

[0156] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, a plurality of secondary batteries 5 may be arranged in order along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 may be fixed by fasteners.

[0157] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.

[0158] In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery pack.

[0159] 5 and 6 show an example of a battery pack 1. Referring to FIG. 5 and FIG. 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may be covered by the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0160] The present application further provides a power consuming device, which includes at least one of the secondary battery, the battery module, or the battery pack according to the present application. The secondary battery, the battery module, or the battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0161] As the power consuming device, a secondary battery, a battery module, or a battery pack can be selected according to the usage demand.

[0162] 7 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the secondary battery of the power consumption device.

[0163] [Example] The following examples of the present application are described. The examples described below are illustrative and are used only to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market. The content of each component in the examples of the present invention is based on the mass without water of crystallization, unless otherwise specified.

[0164] The origins of the raw materials used in the Production Examples and Examples of the present application are as follows.

[0165] [Table 1]

[0166] Example 1-1 Step S1: Preparation of doped manganese oxalate 1.3 mol of MnSO4·H2O and 0.7 mol of FeSO4·H2O are mixed thoroughly in a mixer for 6 hours, the mixture is transferred to a reaction vessel, 10 L of deionized water and 2 mol of oxalic acid dihydrate are added, heated to 80°C, and then stirred at a rotation speed of 600 rpm for 6 hours. The reaction is completed (no bubbles are generated), and a suspension of Fe-doped manganese oxalate is obtained. The suspension is filtered, and the cake is dried at 120°C and crushed to obtain a particle size of D v Fe-doped manganese oxalate particles with sizes of about 50 to 100 nm were obtained.

[0167] Step S2: Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 S 0.001 O 3.999 F 0.001 Manufacturing of cores including 1 mol Fe-doped manganese oxalate particles, 0.497 mol lithium carbonate, 0.001 mol Mo(SO4)3, 0.999 mol phosphoric acid containing 85% phosphoric acid aqueous solution, 0.001 mol H4SiO4, 0.0005 mol NH4HF2 and 0.005 mol sucrose were added to 20 L of deionized water, the mixture was transferred to a sand mill machine and thoroughly ground and stirred for 10 hours to obtain a slurry, the slurry was transferred to a spray drying equipment for spray drying granulation, the drying temperature was set to 250 °C, and dried for 4 hours to obtain particles, and the particles were sintered at 700 °C for 10 hours in a nitrogen gas (90 % v / v) + hydrogen gas (10 % v / v) protective atmosphere to obtain a core material. The element content of the core material was detected using inductively coupled plasma emission spectrum (ICP), and the chemical formula of the core was obtained as above.

[0168] Step S3: Preparation of lithium iron pyrophosphate powder 4.77g of lithium carbonate, 7.47g of ferrous carbonate, 14.84g of ammonium dihydrogen phosphate and 1.3g of oxalic acid dihydrate were dissolved in 50ml of deionized water. The pH of the mixture was 5, and the reaction mixture was stirred for 2 hours to fully react. The solution after the reaction was heated to 80°C and maintained at this temperature for 4 hours to obtain a suspension containing Li2FeP2O7, which was filtered, washed with deionized water, and dried at 120°C for 4 hours to obtain a powder. The powder was sintered at 650°C in a nitrogen gas atmosphere for 8 hours, naturally cooled to room temperature, and then pulverized to obtain Li2FeP2O7 powder.

[0169] Step S4: Preparation of a suspension containing aluminum oxide and sucrose 4.71 g of nanometer-order Al2O3 (particle size about 20 nm) and 3.73 g of sucrose (C 12 H 22 O 11 The aluminum oxide and sucrose were added to 150 ml of deionized water, thoroughly mixed by stirring for 6 hours, and the mixture was heated to 120° C. and maintained at this temperature for 6 hours to obtain a suspension containing aluminum oxide and sucrose.

[0170] Step S5: Fabrication of the two-layer coating layer 157.21 g of the above cores and 1.57 g of the above lithium iron pyrophosphate (Li2FeP2O7) powder were added to the suspension containing aluminum oxide and sucrose obtained in the previous step, stirred to mix uniformly, then transferred to a vacuum oven and dried at 150°C for 6 hours, and the resulting product was dispersed by a sand mill. After dispersion, the product was sintered at 700°C for 6 hours in a nitrogen gas atmosphere to obtain double-coated lithium manganese phosphate.

[0171] Examples 1-2 to 1-59 and Comparative Examples 1 to 12 The positive electrode active materials of Examples 1-2 to 1-59 and Comparative Examples 1 to 12 were produced in a manner similar to that of Example 1-1, and differences in the production of the positive electrode active materials are shown in Table 1-4.

[0172] Here, Comparative Examples 1-9 do not relate to steps S3-S5, Comparative Example 10 does not relate to step S4, and Comparative Example 11 does not relate to step S3.

[0173] [Table 2]

[0174] [Table 3]

[0175] [Table 4]

[0176] [Table 5]

[0177] [Table 6]

[0178] [Table 7]

[0179]

Table 8

[0180]

Table 9

[0181]

Table 10

[0182]

Table 11

[0183]

Table 12

[0184]

Table 13

[0185]

Table 14

[0186]

Table 15

[0187]

Table 16

[0188]

Table 17

[0189]

Table 18

[0190]

Table 19

[0191]

Table 20

[0192]

Table 21

[0193]

Table 22

[0194]

Table 23

[0195]

Table 24

[0196]

Table 25

[0197]

Table 26

[0198]

Table 27

[0199] [Table 28]

[0200] [Table 29]

[0201] [Table 30]

[0202] [Table 31]

[0203] [Table 32]

[0204] [Table 33]

[0205] Example 2-1 In step S3 of preparing lithium iron pyrophosphate (Li2FeP2O7) powder, the sintering temperature in the powder sintering step is 550°C, the sintering time is 1 h, and the crystallinity of Li2FeP2O7 is controlled to 30%, except that the other conditions are the same as those in Example 1-1.

[0206] Example 2-2 In step S3 of preparing lithium iron pyrophosphate (Li2FeP2O7) powder, the sintering temperature in the powder sintering step is 550°C, the sintering time is 2h, and the crystallinity of Li2FeP2O7 is controlled to 50%, except that the other conditions are the same as those in Example 1-1.

[0207] Example 2-3 In step S3 of preparing lithium iron pyrophosphate (Li2FeP2O7) powder, the sintering temperature in the powder sintering step is 600°C, the sintering time is 3h, and the crystallinity of Li2FeP2O7 is controlled to 70%, except that the other conditions are the same as those in Example 1-1.

[0208] Examples 2-4 In step S3 of producing lithium iron pyrophosphate (Li2FeP2O7) powder, the sintering temperature in the powder sintering step is 500° C., and the crystallinity of Li2FeP2O7 is controlled to 10%, except that the other conditions are the same as those in Example 1-1.

[0209] Positive electrode plate manufacturing The positive electrode active material, the double-coated lithium manganese phosphate, the conductive agent, acetylene black, and the adhesive, polyvinylidene fluoride (PVDF), were added to N-methylpyrrolidone (NMP) in a weight ratio of 92:2.5:5.5 and mixed uniformly by stirring to obtain a positive electrode slurry. 2 The mixture was uniformly coated on an aluminum foil, dried, cold pressed and slit to obtain a positive electrode plate.

[0210] Negative electrode plate manufacturing The negative electrode active material, artificial graphite, the conductive agent, superconducting carbon black (Super-P), the adhesive, styrene butadiene rubber (SBR), and the thickener, sodium carboxymethylcellulose (CMC-Na), were dissolved in deionized water in a mass ratio of 95%:1.5%:1.8%:1.7%, and thoroughly stirred to mix uniformly to obtain a negative electrode slurry with a viscosity of 3000 mPa.s and a solid content of 52%. The negative electrode slurry was coated on a negative electrode current collector copper foil of 6 μm, which was then baked at 100 °C for 4 hours, dried, and roll pressed to obtain a compaction density of 1.75 g / cm. 3 A negative electrode plate was obtained.

[0211] Separator Polypropylene film was used.

[0212] Electrolyte production Ethylene carbonate, dimethyl carbonate and 1,2-propanediol carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution, in which the concentration of LiPF6 was 1 mol / L.

[0213] Full battery production The positive electrode plate, separator, and negative electrode plate obtained above were stacked in order so that the separator was located between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell was placed in an exterior body, the electrolyte was injected, and the cell was packaged to obtain a full battery (hereinafter also referred to as a "full cell").

[0214] Button battery manufacturing The positive electrode active material, PVDF, and acetylene black were added to NMP in a weight ratio of 90:5:5, and the mixture was stirred in a drying chamber to prepare a slurry. The slurry was coated on an aluminum foil, dried, and cold pressed to prepare a positive electrode plate. The coating amount was 0.2 g / cm. 2 and the compaction density is 2.0 g / cm 3 It is.

[0215] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in a 1:1:1 volume ratio of ethylene carbonate (EC) + diethyl carbonate (DEC) + dimethyl carbonate (DMC) was used as the electrolyte, and the lithium sheet and the positive electrode plate manufactured above were assembled into a button cell box to form a button battery (hereinafter also referred to as a "button cell").

[0216] Positive electrode active material property test 1. Determination of the chemical formula of the core and the composition of the different coating layers: The internal microstructure and surface structure of the positive electrode active material were characterized with high spatial resolution using a spherical aberrometer (ACSTEM), and combined with three-dimensional reconstruction techniques to obtain the chemical formula of the positive electrode active material core and the composition of the first and second coating layers.

[0217] 2. Button battery initial gram capacity test: The button battery thus prepared was charged at 0.1C from 2.5 to 4.3V to 4.3V, and then charged at a constant voltage of 4.3V until the current was 0.05mA or less. The battery was allowed to stand for 5min, and then discharged at 0.1C to 2.0V. The discharge capacity at this time was taken as the initial capacity and designated as D0.

[0218] 3. Button cell average discharge voltage (V) test: The button battery manufactured above is placed in a constant temperature environment of 25°C for 5 minutes, discharged at 0.1C to 2.5V, placed at rest for 5 minutes, charged at 0.1C to 4.3V, and then charged at a constant voltage of 4.3V until the current is 0.05mA or less, placed at rest for 5 minutes, and then discharged at 0.1C to 2.5V. The discharge capacity at this time is the initial gram capacity, D0, the amount of discharged energy is the initial energy, E0, and the average discharge voltage V of the button cell is E0 / D0.

[0219] 4. Full battery expansion test at 60℃: The full battery manufactured above was stored at 60°C with a state of charge (SOC) of 100%. Before, during and after storage, the open circuit voltage (OCV) and internal resistance (IMP) of the battery core were measured to monitor the SOC, and the volume of the battery core was measured. Here, after every 48 hours of storage, the full battery was taken out and left to stand for 1 hour before testing the open circuit voltage (OCV) and internal resistance (IMP). After cooling to room temperature, the volume of the battery core was measured by the drainage method. In the drainage method, the gravity F1 of the battery core was measured independently using a balance that automatically converts units using the dial data, and then the battery core was completely immersed in deionized water (density 1 g / cm3). 3 The battery core is then placed in a vertical position (known as the gravity force F2) and the buoyancy force F acting on the battery core is measured. 浮 is F1-F2, and Archimedes principle F 浮 =ρ×g×V_ 排 Based on this, the battery core volume V=(F1-F2) / (ρ×g) was calculated.

[0220] From the results of the OCV and IMP tests, the batteries of all the examples maintained an SOC of 99% or more throughout the entire test period until the end of storage.

[0221] After storage for 30 days, the volume of the battery core was measured, and the increase rate of the battery core volume after storage relative to the battery core volume before storage was calculated.

[0222] In addition, the remaining capacity of the battery core was measured. A full battery was charged at 1C from 2.5 to 4.3V up to 4.3V, and then constant voltage charged at 4.3V until the current was 0.05mA or less. The battery was left to stand for 5min, and the charge capacity at this time was recorded as the remaining capacity of the battery core.

[0223] 5. Cycle performance test of full battery at 45℃: In a constant temperature environment of 45°C, the full battery prepared above was charged at 1C to 4.3V at 2.5 to 4.3V, and then constant voltage charged at 4.3V until the current was 0.05mA or less. It was left to stand for 5min, and then discharged at 1C to 2.5V, and the discharge capacity at this time was recorded as D0. The above charge-discharge cycle was repeated until the discharge capacity decreased to 80% of D0. The number of cycles the battery had gone through was recorded.

[0224] 6. Lattice change rate test: In a constant temperature environment of 25°C, the prepared positive electrode active material sample was placed in an XRD (model number: Bruker D8 Discover) and the sample was tested at 1° / min. The test data was compiled and analyzed, and the lattice constants a0, b0, c0 and v0 (a0, b0 and c0 represent the length magnitude in each direction of the unit lattice, and v0 represents the volume of the unit lattice, which can be obtained directly from the XRD finishing results) were calculated with reference to the specification PDF card.

[0225] Using the above button cell manufacturing method, a positive electrode active material sample was manufactured as a button cell, and the button cell was charged at a low rate of 0.05C until the current decreased to 0.01C. The positive electrode plate in the button cell was then taken out and placed in dimethyl carbonate (DMC) for 8 hours. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The volume v1 of the unit lattice was calculated in the same manner as the fresh test sample, and (v0-v1) / v0×100% was shown in the table as the lattice change rate (volume change rate of the unit lattice) before and after the lithium was completely released.

[0226] 7. Li / Mn antisite defect concentration test: The XRD results tested using the "lattice change rate measurement method" were compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested using the "lattice change rate measurement method" were introduced into the General Structure Analysis System (GSAS) software to automatically obtain the refinement results, which included the occupancy status of different atoms, and the Li / Mn antisite defect concentration was obtained by reading the refinement results.

[0227] 8. Transition metal elution test: The full battery, which had been cycled at 45°C until the capacity had decayed to 80%, was discharged at a rate of 0.1 C to a cut-off voltage of 2.0 V. The battery was then disassembled, the negative electrode plate was removed, and 30 unit area (1540.25 mm2) pieces were placed on the negative electrode plate. 2 ) wafers were randomly taken and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. Based on the ICP results, the amount of Fe (if Fe is doped on the Mn site of the positive electrode active material) and Mn were calculated, and the amount of Mn (and Fe doped on the Mn site) dissolved after cycling was calculated accordingly. The test standard complies with EPA-6010D-2014.

[0228] 9. Surface oxygen valence state test: 5 g of the above-prepared positive active material sample was taken and prepared into a button cell according to the above-mentioned button cell preparation method. The button cell was charged at a low rate of 0.05 C until the current decreased to 0.01 C. The positive electrode plate in the button cell was then taken out and placed in dimethyl carbonate (DMC) for 8 hours. It was then dried, the powder was scraped off, and particles with a particle size of less than 500 nm were selected. The obtained particles were measured by electron energy loss spectroscopy (EELS, the model number of the equipment used was Talos F200S) to obtain the energy loss near edge structure (ELNES), which reflected the state density and energy level distribution of the elements. From the state density and energy level distribution, the valence band state density data was integrated to calculate the number of occupied electrons, and the valence state of the surface oxygen after charging was estimated.

[0229] 10. Compaction density measurement: 5 g of the above-prepared positive active material powder was taken and placed in a compaction mold (USA CARVER mold, model number 13 mm), and the mold was placed on a compaction density meter. A pressure of 3 T was applied, and the powder thickness at pressure was read on the instrument (thickness after decompression, the area of ​​the test container was 1540.25 mm 2 ) and ρ = m / v, the compacted density was calculated.

[0230] 11. Examination of the crystallinity of pyrophosphates and phosphates by X-ray diffraction method 5 g of the above-prepared positive electrode active material powder is taken and the total scattering intensity is measured by X-ray, which is the sum of the scattering intensity of the material in the entire space and has nothing to do with the order state of the sample, but only with the intensity of the primary radiation, the chemical structure, and the total number of electrons involved in diffraction, i.e., the amount of mass. Crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, and the crystallinity is the ratio of the crystalline partial scattering to the total scattering intensity.

[0231] 12. Lattice spacing and angles 1 g of each of the positive electrode active material powders prepared above was placed in a 50 mL test tube, and 10 mL of alcohol with a mass fraction of 75% was poured into the test tube. The tube was thoroughly stirred and dispersed for 30 minutes. Then, an appropriate amount of the above solution was taken with a clean disposable plastic straw and dropped onto a 300 mesh copper net. At this time, some of the powder remained on the copper net. The copper net was transferred together with the sample into a TEM (Talos F200s G2) sample cavity for testing. The original image of the TEM test was obtained and the original image format (xx.dm3) was saved.

[0232] The original image obtained in the above TEM test was opened in DigitalMicrograph software and Fourier transformed (the software automatically completes it after a click) to obtain a diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern was measured to obtain the lattice spacing, and the angle between them was calculated using the Bragg equation.

[0233] The above results are shown in Table 5-9.

[0234] [Table 34]

[0235] [Table 35]

[0236] [Table 36]

[0237] [Table 37]

[0238] [Table 38]

[0239] [Table 39]

[0240] [Table 40]

[0241] [Table 41]

[0242] [Table 42]

[0243] [Table 43]

[0244] [Table 44]

[0245] As can be seen from Examples 1-1 to 1-59 and Comparative Examples 1-9, the presence of the first coating layer is beneficial for reducing the Li / Mn antisite defect concentration of the resulting material and the amount of Fe and Mn eluted after cycling, improving the button cell gram capacity of the battery, and improving the high-temperature storage performance, safety performance, and cycle performance of the battery. When other elements are doped into the Li site, Mn site, phosphorus site, and oxygen site, respectively, the lattice change rate, antisite defect concentration, and amount of Fe and Mn eluted from the resulting material can be obviously reduced, the gram capacity and compaction density of the battery can be improved, and the high-temperature storage performance, safety performance, and cycle performance of the battery can be improved.

[0246] As can be seen from Examples 1-33 to 1-36, as the amount of the first coating layer increases from 3.2% to 6.4%, the amount of Fe and Mn dissolved in the obtained materials after cycling gradually decreases, and the high-temperature storage performance, safety performance and cycle performance at 45°C of the corresponding batteries are also improved, but the button cell capacity is slightly reduced. Alternatively, when the total amount of the first coating layer is 4-6.4 wt%, the overall performance of the corresponding batteries is optimal.

[0247] As can be seen from Example 1-1 and Examples 1-37 to 1-40, as the amount of the second coating layer increases from 1% to 6%, the amount of Fe and Mn dissolved after cycling of the obtained materials gradually decreases, and the high temperature storage performance, safety performance and cycle performance at 45°C of the corresponding batteries are also improved, but the button cell capacity is slightly reduced. Alternatively, when the total amount of the second coating layer is 3-5 wt%, the overall performance of the corresponding batteries is optimal.

[0248] As can be seen from Example 1-1 and Examples 1-41 to 1-44, when Li2FeP2O7 and Al2O3 were present simultaneously in the first coating layer, especially when the weight ratio of Li2FeP2O7 to Al2O3 was 1:3 to 3:1, the battery performance was obviously improved.

[0249] [Table 45]

[0250] As can be seen from Table 6, with the gradual increase in the crystallinity of the pyrophosphate in the first coating layer, the lattice change rate of the corresponding material, the Li / Mn antisite defect concentration and the amount of Fe and Mn dissolved gradually decreased, the button cell capacity of the battery gradually increased, and the safety performance and cycle performance were also gradually improved.

[0251] [Table 46]

[0252] [Table 47]

[0253] [Table 48]

[0254] [Table 49]

[0255] As can be seen from Table 7, by adjusting the stirring rotation speed in the reaction vessel, reaction temperature, grinding time, and sintering temperature and time during the core preparation process, each performance of the positive electrode material of the present application can be further improved.

[0256] [Table 50]

[0257] [Table 51]

[0258] As can be seen from Tables 8-9, when lithium iron pyrophosphate is prepared by the method of the present application, by adjusting the drying temperature / time and sintering temperature / time in the preparation process, the performance of the obtained material can be improved, thereby improving the battery performance; by adjusting the drying temperature / time and sintering temperature / time in the coating process, the performance of the obtained material can be improved, thereby improving the battery performance.

[0259] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]

[0260] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 Cover plate , 11 core, 12 first coating layer, 13 second coating layer.

Claims

1. A positive electrode active material having a core-shell structure, comprising a core and a shell covering the core, The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.5-1.2, x is selected from any number in the range of 0.001-0.5, y is selected from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.2, and n is selected from any number in the range of 0.001-0.5, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo, and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb, and Ge, C is one or more elements selected from B, S, Si, and N, and D is one or more elements selected from S, F, Cl, and Br, the shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer, Here, the first coating layer is made of crystalline pyrophosphate M a P 2 O 7 and oxide M' b O c wherein a is greater than 0 and less than or equal to 4, b is greater than 0 and less than or equal to 2, c is greater than 0 and less than or equal to 5, M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and M' is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides, and Sb; The positive electrode active material, wherein the second coating layer contains carbon.

2. In the core, the ratio of 1-y to y is from 1 to 4, and / or 2. The positive electrode active material according to claim 1, wherein the ratio of m to x is 1 to 1200.

3. and / or, x is any number in the range of 0.001-0.005; and / or, y is any number in the range of 0.01-0.5; and / or and / or, z is any number in the range of 0.001-0.005; and / or 2. The positive electrode active material according to claim 1, wherein n is an arbitrary value within a range of 0.001 to 0.

005.

4. 2 . The positive electrode active material according to claim 1 , wherein a coating amount of the first coating layer is greater than 0% by weight and less than or equal to 7% by weight, based on the weight of the core.

5. 2. The positive electrode active material according to claim 1, wherein the weight ratio of pyrophosphate to oxide in the first coating layer is 1:3 to 3:

1.

6. 2. The positive electrode active material according to claim 1, wherein the lattice spacing of the pyrophosphate in the first coating layer is 0.293-0.326 nm and the angle with respect to the crystal direction (111) is 26.41°-32.57°.

7. 2. The positive electrode active material according to claim 1, wherein the crystallinity of the pyrophosphate in the first coating layer is 10% to 100%.

8. 2. The positive electrode active material according to claim 1, wherein a coating amount of the second coating layer is greater than 0% by weight and not more than 6% by weight, based on the weight of the core.

9. The A is any one element selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and / or The B is at least two elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and / or The C is any one element selected from B, S, Si and N, and / or The positive electrode active material according to claim 1 , wherein D is any one element selected from the group consisting of S, F, Cl and Br.

10. 2. The positive electrode active material according to claim 1, wherein the positive electrode active material has a Li / Mn antisite defect concentration of 4% or less.

11. The positive electrode active material according to claim 1 , wherein a lattice change rate of the positive electrode active material before and after complete release of lithium is 9.8% or less.

12. 2. The positive electrode active material according to claim 1, wherein the valence state of surface oxygen of the positive electrode active material is −1.55 or less.

13. The compaction density of the positive electrode active material in 3 tons is 1.89 g / cm 3 The positive electrode active material according to claim 1 .

14. A method for producing a positive electrode active material, comprising: Providing a core material, the core comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.5-1.2, x is selected from any number in the range of 0.001-0.5, y is selected from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.2, n is selected from any number in the range of 0.001-0.5, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C is one or more elements selected from B, S, Si and N, and D is one or more elements selected from S, F, Cl and Br; Pyrophosphate M a P 2 O 7 A powder containing a carbon source and an oxide M' b O c providing a suspension comprising the core material and pyrophosphate M a P 2 O 7 A powder containing a carbon source and an oxide M' b O c and a coating step of mixing the resulting mixture with a suspension containing the above-mentioned a and sintering the mixture to obtain a positive electrode active material, wherein a is greater than 0 and equal to or less than 4, b is greater than 0 and equal to or less than 2, c is greater than 0 and equal to or less than 5, M is one or more elements selected from Li, Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and M′ is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanide elements, and Sb; Here, the positive electrode active material has a core-shell structure, and the positive electrode active material includes a core and a shell that covers the core, and the core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes a first coating layer that coats the core and a second coating layer that coats the first coating layer, and the first coating layer is a crystalline pyrophosphate M a P 2 O 7 and oxide M' b O c and wherein the second coating layer contains carbon.

15. The step of providing a core material comprises: (1) mixing a manganese source, a source of element B, an acid and a solvent to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, a source of element D, and a solvent, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

16. The source of element A is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element A; and / or The source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The method according to claim 14, wherein the source of the element D is one or more selected from an elemental substance of the element D and an ammonium salt thereof.

17. The pyrophosphate M a P 2 O 7 The powder comprising The method of claim 14, which is produced by the steps of mixing a source of element M, a phosphorus source and a solvent to obtain a mixture, adjusting the pH of the mixture to 4-6, continuing to mix, drying and sintering.

18. The method of claim 14, wherein the sintering temperature in the coating step is 500°C-800°C, and the sintering time is 4-10h.

19. 13. A positive electrode plate comprising: a positive electrode current collector; and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material according to claim 1, and a content of the positive electrode active material in the positive electrode film layer is 10 wt % or more based on a total weight of the positive electrode film layer.

20. A secondary battery comprising the positive electrode active material according to claim 1.

21. A battery module comprising the secondary battery according to claim 20.

22. A battery pack comprising the battery module according to claim 21.

23. 23. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 20, the battery module according to claim 21, and the battery pack according to claim 22.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate composite material, preparation method thereof and lithium ion battery

    CN114256448A

  • Positive electrode active material and nonaqueous electrolyte secondary battery

    JP2002198050A

  • Positive electrode active material for lithium ion secondary batteries, positive electrode for lithium ion secondary batteries, lithium ion secondary battery, and method for manufacturing positive electrode active material for lithium ion secondary batteries

    JP2015082476A

  • Positive electrode material for lithium ion batteries, method for manufacturing the same and application thereof

    JP2016127002A

  • Lithium ion secondary battery

    JP2017143049A